Percutaneous creation of proximal radio-radial arteriovenous hemodialysis fistula before secondary brachial vein elevation. Issue 2 (March 2021) - Mallios, Alexandros; Bourquelot, Pierre; Harika, Ghazi; Boura, Benoit; Jennings, William C
Objective: We evaluate the creation of a percutaneous proximal radial artery–radial vein arteriovenous fistula with Ellipsys ® instead of the usual first-stage brachial artery fistula prior to a second-stage brachial vein elevation, in patients with inadequate cephalic and basilic veins. Methods: Single center study of eight patients (six males, mean = 54 years) who underwent a two-stage brachial vein elevation procedure between May 2017 and October 2019. Inclusion criteria were life expectancy > 6 months, patent brachial and proximal radial artery (>2 mm in diameter) absent/inadequate cephalic and basilic veins, existence of a brachial vein >3 mm in diameter, and in continuity with a proximal radial vein > 2 mm in diameter. Results: Technical success was 100%. Four patients required angioplasty of a juxta-anastomotic stenosis, accounting for a 6-month primary and secondary patency rates were 68% and 100%, respectively. Access flow averaged 982 mL/min (range 768–1586) at final follow-up evaluation. There were no significant adverse events related to the procedures. All fistulae were elevated at 4–12 (mean: 8) weeks post creation and were successfully cannulated with two needles after healing was completed (2–4 weeks after elevation). No patients developed hand ischemia or arm edema. Conclusions: Percutaneous creation of a proximal radial artery–radial vein fistula followed by brachial vein elevation is a safe and reliable option for autogenous access creation in patients with inadequate cephalic or basilic veins. Minimally invasive radial artery inflow and longer available length of the targeted brachial vein available for elevation are the main advantages in skilled hands.